Neuroplasticity and rehabilitation - Raskin, Sarah A. (Guilford Press, 2011)
"Brain plasticity is the focus of a growing body of research with significant implications for neurorehabilitation. This state-of-the-art volume explores ways in which brain-injured individuals may be helped not only to compensate for their loss of cognitive abilities, but also possibly to restore those abilities. Expert contributors examine the extent to which damaged cortical regions can actually recover and resume previous functions, as well as how intact regions are recruited to take on tasks once mediated by the damaged region. Evidence-based rehabilitation approaches are reviewed for a range of impairments and clinical populations, including both children and adults"--Provided by publisher.